Penataan Hewan Ternak Masyarakat Dalam Perspektif Kewenangan Desa Berskala Lokal (Studi di Desa Sungai Ara Kabupaten Indragiri Hilir) - Syaiful Mudzhab; Jamri; Ali Azhar (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
Community Livestock Management from the Perspective of village Authority on a Local Scale: A Study in Sungai Ara Village, Indragiri Hilir Regency. The management of community livestock is one form village community development aimed at ensuring that livestock raising activities do not create problems such as environmental pollution and public disorder. However, in practice various issues are still found due to livestock management that has not been properly organized. This study aims to identify the forms of community livestock management from the perspective of local-scale village authority in Sungai Ara Village, Indragiri Hilir Regency, to determine the obstacles encountered in implementing livestock management and to identify effors that can be undertaken to improve livestock management within the framework of local-scale village authority. This research employs a sociological or empirical approach with a descriptive research design. Data were collected through interviews with the Village Head, Hamlet Head, Neighborhood Association (RT) leaders, Community Association (RW) leaders, community figures, and residents and residents who raise livestock in Sungai Ara Village, Indragiri Hilir Regency. In addition, a literature review was conducted using Law Number 6 of 2014 concerning Villages. Books and journals related to community livestock management and local-scale village authority. The data were analyzed qualitatively. The results of the study indicate that the village government has the authority to regulate the administration of governmental affairs and the interests of the local community. In line with Law Number 6 of 2014, villages possess local-scale authority, enabling them to independently manage village affairs, including resolving issues related to community livestock management. This can be achieved through the formulation of a village regulation (Peraturan Desa/PERDES) concerning community livestock management in Sungai Ara Village, Indragiri Hilir Regency. The obstacles to community livestock management include insufficient community between the Sungai Ara Village Government and livestock owners, as well as the absence of a village regulation governing community livestock management. To address these obstacles, effors should be made to strengthen communication between the village government and livestock owner and to enact a village regulation on community livestock management in Sungai Ara Village, Indragiri Hilir Regency.